2022
DOI: 10.4018/978-1-6684-5876-1.ch018
|View full text |Cite
|
Sign up to set email alerts
|

Internal Audit, Internal Control Systems in Finance Industry in the Changing Business Environment, Evidence From Turkey as an Emerging Economy

Abstract: The purpose of this chapter is to review internal audit and internal control functions in the banking industry by taking into account the international COSO framework. The financial industry is regarded as one of the key elements of a stable economy. It is a well-known fact that financial institutions in general—banks in particular (public or private, foreign or local)—need to have a sound internal system to implement the high principle of ‘maker-checker-supervisor-auditor'. The study examines the application … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…One of the purposes of internal control systems is to reduce the risk of inability to achieve the company's predetermined objectives, in light of its strategies and related policies, and to manage these risks in a way that allows those responsible for managing the company to be rational in dealing with them. It is an ongoing process aimed at identifying, evaluating their nature and scope, and managing them efficiently, effectively, and economically (D'Aquila, 2013) (Kayhan, 2023;Ciobu & Tataru, 2021;Hamdan , 2019;Salman, 2021). Internal control provides independent safeguards and advice that help organizations manage crises effectively.…”
Section: Internal Control and Covid-19 Pandemicmentioning
confidence: 99%
“…One of the purposes of internal control systems is to reduce the risk of inability to achieve the company's predetermined objectives, in light of its strategies and related policies, and to manage these risks in a way that allows those responsible for managing the company to be rational in dealing with them. It is an ongoing process aimed at identifying, evaluating their nature and scope, and managing them efficiently, effectively, and economically (D'Aquila, 2013) (Kayhan, 2023;Ciobu & Tataru, 2021;Hamdan , 2019;Salman, 2021). Internal control provides independent safeguards and advice that help organizations manage crises effectively.…”
Section: Internal Control and Covid-19 Pandemicmentioning
confidence: 99%
“…The age distribution showed that the largest age group was 25-34 years (31.6%), followed by 35-44 years (25.5%), 45-54 years (22.6%), and 55 years and above (20.3%) [2]. In terms of education level, the majority of participants held a Master's degree (41.4%), followed by a Bachelor's degree (36.1%), and a Doctoral degree (22.5%) [3]. The distribution of positions revealed that mid-level positions were the most common (39.1%), followed by senior positions (36.8%) [4].…”
Section: Demographic Samplementioning
confidence: 99%
“…Prior studies have demonstrated that internal control systems have a positive impact on both financial performance and technological innovation [1], [2]. The relevance of internal control systems in reducing financial fraud holds significant value, especially within the framework of increased financialization [3]. Internal audit and control functions play a crucial role in the banking sector by facilitating the implementation of robust internal systems and safeguarding the stability of financial organizations [4].…”
Section: Introductionmentioning
confidence: 99%